Efeito da glucose-oxidase sobre a produção de celulase - Hauly, Maria Célia de Oliveira; Oliveira, Antonio Sérgio de; Silva, Rui Sérgio dos Santos Ferreira da; Caminotto, Rosângela (Semina: Ciências Agrárias, 1983)
With the object to decrease the glucose inhibitory effect over cellulose, Trichoderma reesei QM 9414 was cultivated in the presence of 72,000 units (4g) of glucose-oxidase per liter culture media. Measurements were made for enzyme activity, protein and residual cellulose for all the fermentations in the presence or in the absence of glucose-oxidase. Analysis of vaÂriance (F-testj had shown that the enzyme activity and specific activity were not statistically significant at 5% level (p<0,05) under these two different fermentation conditions.